(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Livestock systems require a thorough analysis of zootechnical and financial indicators. In this sense, the objective of this study was to evaluate the bioeconomic performance of feedlot bulls with different genetic groups in 2012 and 2013. The experiment was carried out on a farm in Paragominas, State of Pará. The confined animals belonged to the Nellore (NE), ½ Angus ½ Nellore (AN) and ½ Charolais ½ Nellore (CH) breeds. The indicators analyzed were the cost of production and economic indicators. Additionally, zootechnical indicators were evaluated, being considered NE, AN, and CH as treatments in a completely randomized design. The financial results of the total production cost were R 118,493.21 in 2012, and R 111,166.35 in 2013, and the profitability obtained was 11% in 2012 and 8% in 2013. Regarding the zootechnical indicators, the CH genetic group showed superiority (P <0.01) compared to the NE genetic group for the variables initial weight (IW), final weight (FW), weight gain (WG), average daily weight gain (DWG), and carcass yield (CY). The confinement proved to be economically viable, with positive margins and satisfactory profitability, and the CH genetic group had the best indicators and the highest increase in the final revenue of the activity.